Effect of nitrogen supplementation on aerobic degradation of LAS by consortia of bacteria - Kehinde Temitope Eniola (MDPI AG, 2012)
Untreated detergent-bearing wastes discharged into the environment serve as sources of LAS. Detergent wastes usually do not contain nitrogen or contain very low amounts. Biostimulation by introducing limiting nutrient element can be useful in biotreatment of such waste. The effect of inorganic and organic nitrogen supplements on aerobic degradation of linear alkylbenzene sulfonate (LAS) by LAS-utilizing bacteria (LUB) was examined. Phosphate-buffered LAS mineral media were prepared and supplemented with different nitrogen sources: NPK fertilizer (inorganic) and Urea fertilizer (organic). Individual and various consortia of pure cultures of Alcaligenes odorans, Citrobacter diversus, Micrococcus luteus and Pseudomonas putida previously isolated from detergent-effluent polluted stream were used. Biodegradation of LAS was monitored in terms of half-life (t½) of the surfactant. The rates of biodegradation by the consortia can be ranked as: four-membered (t½= 8- 12 days) > three-membered (t½= 8 to 13 days) > two-membered consortia (t½= 10 to 15 days) > individuals (t½= 9 to 16 days). The inorganic nitrogen source enhanced utilization of the surfactant, while organic nitrogen supplementation generally slowed degradation of the surfactant. In undertaking bio-treatment of detergent-bearing effluent; inorganic nitrogen should be used as biostimulant.